2018
DOI: 10.1111/apt.14685
|View full text |Cite
|
Sign up to set email alerts
|

High efficacy of direct‐acting anti‐viral agents in hepatitis C virus‐infected cirrhotic patients with successfully treated hepatocellular carcinoma

Abstract: This large real-life study proves that the efficacy of DAA in cirrhotic patients is not impaired by successfully treated HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 30 publications
2
32
1
Order By: Relevance
“…Study characteristics were summarised in Tables and . Fifty‐six studies were included, with a total of 5522 patients with HCC, while 27 studies enrolled non‐HCC patients as control groups. Fifty‐three (95%) studies were observational cohorts (45 retrospective and eight prospective) and three studies were clinical trials.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Study characteristics were summarised in Tables and . Fifty‐six studies were included, with a total of 5522 patients with HCC, while 27 studies enrolled non‐HCC patients as control groups. Fifty‐three (95%) studies were observational cohorts (45 retrospective and eight prospective) and three studies were clinical trials.…”
Section: Resultsmentioning
confidence: 99%
“…Study characteristics were summarised in Tables 1 and 2. Fifty-six studies 11,13,28,30,31, were included, with a total of 5522 patients with HCC, while 27 studies enrolled non-HCC patients as control groups.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, HCC patients showed a high SVR rate with DCV/ASV combination therapy, because they had mostly compensated liver disease with high adherence to antiviral therapy. Similarly, recent studies have shown that antiviral efficacy in HCC patients after curative treatment with DAAs is comparable to those without HCC . Thus, antiviral treatment should be offered to HCC patients who were curatively treated with enough life expectancy.…”
Section: Discussionmentioning
confidence: 97%
“…Because ASV is not labeled for decompensated cirrhosis, previous data are limited, but a recent study reported 100% of SVR in 10 decompensated cirrhosis, 24 DAAs is comparable to those without HCC. 25,26 Thus, antiviral treatment should be offered to HCC patients who were curatively treated with enough life expectancy.…”
Section: Treatment Withdrawal and Adverse Events During DCV Plus Asmentioning
confidence: 99%